2022
DOI: 10.24272/j.issn.2095-8137.2021.434
|View full text |Cite
|
Sign up to set email alerts
|

Avian sibling cannibalism: Hoopoe mothers regularly use their last hatched nestlings to feed older siblings

Abstract: Sibling cannibalism is relatively common in nature, but its evolution in birds and certain other vertebrates with extended parental care had been discarded. Here, however, we demonstrate its regular occurrence in two European populations of the Eurasian hoopoe ( Upupa epops ) and explore possible adaptive and non-adaptive explanations. Results showed that sibling cannibalism was more frequently detected in Spain (51.7%) than in Austria (5.9%). In these two populations, the hoopoes laid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Which is the functionality of such nestlings or of last laid eggs? The high rates of hatching failures in hoopoe nests, which in our study area are close to two eggs on average ( Martín-Vivaldi et al 1999 ; Soler et al 2008 , Soler, Martín-Vivaldi, et al 2022 ) might suggest an insurance function of the last laid eggs ( Forbes 1990 , 1991 ; Hardy 1992 ). This is likely the case because the intensity of brood reduction, that we detected up to 2 days after the end of hatching, associated negatively with hatching failures (β(SE) = −0.365 (0.143), F = 6.50, df = 1, 44, P = 0.014), even after controlling for the effect of hatching date (β(SE) = 0.287 (0.143), F = 4.02, df = 1, 44, P = 0.051).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Which is the functionality of such nestlings or of last laid eggs? The high rates of hatching failures in hoopoe nests, which in our study area are close to two eggs on average ( Martín-Vivaldi et al 1999 ; Soler et al 2008 , Soler, Martín-Vivaldi, et al 2022 ) might suggest an insurance function of the last laid eggs ( Forbes 1990 , 1991 ; Hardy 1992 ). This is likely the case because the intensity of brood reduction, that we detected up to 2 days after the end of hatching, associated negatively with hatching failures (β(SE) = −0.365 (0.143), F = 6.50, df = 1, 44, P = 0.014), even after controlling for the effect of hatching date (β(SE) = 0.287 (0.143), F = 4.02, df = 1, 44, P = 0.051).…”
Section: Discussionmentioning
confidence: 59%
“…Preferential feeding of females for larger nestlings might seem contradictory to previous results published by Ryser et al (2016) , where they demonstrated that females are more selective than male hoopoes when it comes to food allocation to the smallest chick. However, those authors studied food allocation by adult hoopoes after most of the brood reduction had occurred (i.e., when females leave the nests and together with males bring food to feed leftover nestlings) and, then, it is possible that food allocation behavior of females changes at that nestling stage (see also Soler, Martín-Vivaldi, et al 2022a ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Siblicidal brood reduction has long been studied in birds, in which cannibalistic events occur occasionally and are considered of limited importance Environmental Entomology, 52(2), 2023, 157-168 https://doi.org/10.1093/ee/nvad002 Advance Access Publication Date: 28 January 2023 Research nutritionally (Bortolotti et al 1991, Stanback and Koenig 1992, Mock and Parker 1997. Thus, the dichotomization of the sibling rivalry context may be affected by a taxonomic bias in studies of sibling rivalry (see Morandini and Ferrer 2015), although sibling cannibalism in birds may occur much more frequently than previously thought, as shown by recent studies (Anderson et al 2015, Allen et al 2020, Soler et al 2022. Siblicide and sibling cannibalism share costs (risk of injury and loss of inclusive fitness) and benefits (reduction in resource competition), but cannibalism also has other costs (risk of infection) and benefits (gains in nutrition) (Fox 1975, Polis 1981, Edgar and Crespi 1992, Mock and Parker 1997, Forbes 2005.…”
mentioning
confidence: 99%